2015
DOI: 10.1007/s12178-015-9259-x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma for muscle injuries: game over or time out?

Abstract: Muscle injuries are common and may be associated with impaired functional capacity, especially among athletes. The results of healing with conventional therapy including rest, ice, compression, and elevation (RICE) are often inadequate, generating substantial interest in the potential for emerging technologies such as platelet-rich plasma (PRP) to enhance the process of soft-tissue healing and to decrease time to recovery. In vitro studies and animal research have suggested that PRP may have benefits associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Dimauro et al (2014) [55] reported that PRP treatment reduced the level of several apoptotic markers during muscle regeneration process. Platelets present in PRP are known as a chief source of biologically active metabolites that modulate inflammation, cellular proliferation, migration, angiogenesis, vascular remodeling, antimicrobial action and ECM synthesis [56] .…”
Section: Study Of Gigante Et Al (2012)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dimauro et al (2014) [55] reported that PRP treatment reduced the level of several apoptotic markers during muscle regeneration process. Platelets present in PRP are known as a chief source of biologically active metabolites that modulate inflammation, cellular proliferation, migration, angiogenesis, vascular remodeling, antimicrobial action and ECM synthesis [56] .…”
Section: Study Of Gigante Et Al (2012)mentioning
confidence: 99%
“…One of the identified platelet secretory granules are alpha granules that contain plateletderived growth factor (PDGF), transforming growth factorbeta (TGFB), epidermal growth factor (EGF),vascular endothelial growth factor(VEGF),cytokines and others [23] . This knowledge stimulated the development of a platelet concentrate intended for increasing levels of local growth factors (GFs) delivery at the injury site to improve tissue repair, regeneration and remodeling [24,25] .Therefore, the present study was conducted to elucidate the morphometric and histological changes after local application of PRP in induced traumatic skeletal muscle injury in rats in a trial to describe the efficacy of PRP in the treatment of such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions such as Platelet Rich Plasma (PRP) and Autologous Conditioning Serum (ACS) have become popular augmentative therapies in Sports Medicine, being proposed to facilitate muscle healing by optimizing provision of growth factors from promising animal study [13][14][15]. However, again these results do not necessarily translate to human trial.…”
Section: Muscle Injuries -Current Strategies and Issuesmentioning
confidence: 99%
“…Protocols vary greatly with regard to velocity and duration of centrifugation. This variation alters the composition of platelet concentrates, leading to patterns of growth factor expression 6567 , some of which may have an adverse effect by potentially enhancing the fibrotic response 67 . While promising, the optimal preparation of platelet concentrates and the time during healing wherein they might promote an effective response have not been identified.…”
Section: Therapeuticsmentioning
confidence: 99%